Perlindungan Hukum dan Implementasi Doktrin Fair Use Terhadap Costume Play (Cosplay) dalam Hak Cipta dan Desain Industri - Ramadhan, Galih Dwi (JIPRO: Journal of Intellectual Property, 2021)
Cosplay 'Costume & Play' is a term that describes a pop-culture phenomenon about a person's creativity by creating and using a costume and its accessories to play a role based on references to fictional characters from comic books, animated films, and video games. Costumes and accessories used for cosplay are the work of human intellectuals which should be protected by intellectual property rights because in practice many parties get financial benefits from cosplay activities. There is no explicit regulation on the protection of intellectual works, especially Copyright and Industrial Design Rights for cosplay costumes and accessories. A normative juridical study is needed in understanding the legal provisions on cosplay using the Copyright Law and the Industrial Design Law.